Outcomes of Total Knee Arthroplasty in Relation to Preoperative Patient-Reported and Radiographic Measures - Timothy L. Kahn BA; Aydin Soheili MD; Ran Schwarzkopf MD, MSc (Geriatric Orthopaedic Surgery & Rehabilitation, 2013)
Introduction: Total knee arthroplasty (TKA) is the preferred surgical treatment for end-stage osteoarthritis. However, substantial numbers of patients still experience poor outcomes. Consequently, it is important to identify which patient characteristics are predictive of outcomes in order to guide clinical decisions. Our hypothesis is that preoperative patient-reported outcome measures and radiographic measures may help to predict TKA outcomes. Methods: Using cohort data from the Osteoarthritis Initiative, we studied 172 patients who underwent TKA. For each patient, we compiled pre- and postoperative Western Ontario and McMaster University Arthritis Index (WOMAC) scores. Radiographs were measured for knee joint angles, femorotibial angles, anatomical lateral distal femoral angles, and anatomical medial proximal tibial angles; Kellgren and Lawrence (KL) grades were assigned to each compartment of the knee. All studied measurements were compared to WOMAC outcomes. Results: Preoperative WOMAC disability, pain, and total scores were positively associated with postoperative WOMAC total scores ( P = .010, P = .010, and P = .009, respectively) and were associated with improvement in WOMAC total scores ( P < .001, P < .001, and P < .001, respectively). For radiographic measurements, preoperative joint angles were positively associated with improvements in postoperative WOMAC total scores ( P = .044). Combined KL grades (medial and lateral compartments) were negatively correlated with postoperative WOMAC disability and pain scores ( P = .045 and P = .044) and were positively correlated with improvements in WOMAC total scores ( P = .001). Conclusions: All preoperative WOMAC scores demonstrated positive associations with postoperative WOMAC scores, while among the preoperative radiographic measurements only combined KL grades and joint angles showed any correlation with postoperative WOMAC scores. Higher preoperative KL grades and joint angles were associated with better (lower) postoperative WOMAC scores, demonstrating an inverse correlation.